House Sparrows "Passer Domesticus" breeding in nests of the Red-rumped Swallow "Hirundo daurica" - Samson, Arockianathan; Ramakrishnan, Balasundaram; Manigandan, Selvaraj (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The House Sparrow "Passer domesticus", a member of the family Passeridae, has a worldwide distribution and colonized all continents and many oceanic Islands (Cramp et al. 1985). However, a large decrease in House Sparrow populations is reported from a variety of countries worldwide (Crick et al. 2002, Prowse 2002, Summers-Smith 2003).
Keywords: wróblowe; ornitologia